Upaya Meningkatkan Hasil Belajar Siswa pada Materi Pembentukan Tanah Karena Pelapukan Batuan dengan Model Kooperatif Tipe Two Stay Two Stray di Kelas VI SD Negeri 39 Lubuklinggau - Nurbayati Nurbayati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The low level of activity of grade 6 students of SD Negeri 39 Lubuklinggau in science lesson, and the learning model used is less varied resulting in low student learning outcomes in science lesson, therefore the researcher intends to improve learning by conducting classroom action research consisting of three cycles by using Model Cooperative Type Two Stay Two Stray. The study was conducted on February 2, 2015, cycle 1 on February 9, 2015, and cycle of 10 February 2015 with the following results: first activity of students from prasiklus, cycle 1 and cycle 2 progressed on prasiklus 56.67%, students active in cycle 1 increased to 70% and cycle 2 to 86.67% of active students. Both the average test held in each cycle also experienced a significant increase of average prasiklus only 51.83, in cycle 1 increased to 62.5 and in cycle 2 to 80.83. Completeness also experienced an increase in prasiklus only 43.33%, cycle 1 increased to 66.67%, and in cycle 2 reached 93.33%. So it can be concluded the use of cooperative model type Two Stay Two Stray managed to improve the ability to encourage student achievement, especially Class VI SD Negeri 39 Lubuklinggau. Keywords: Learning Outcomes, TSTS Model